Brief Report: Atypical Expression of Distress During the Separation Phase of the Strange Situation Procedure in Infant Siblings at High Risk for ASD - Esposito, Gianluca (2017)
Previous studies have provided preliminary evidence that disruptions in cry acoustics may be part of an atypical vocal signature of autism early in life. We examined the acoustic characteristics of cries extracted from the separation phase of the strange situation procedure in a sample of toddler of younger siblings of a child with autism spectrum disorder-autism spectrum disorders (ASD) (high risk, HR) and a low risk (LR) group. Cry samples derived from vocal recordings of 15-month-old HR (n = 13) and LR infants (n = 14) were subjected to acoustic analyses. HR toddlers, compared to those with LR, produced cries that were shorter and had a higher fundamental frequency (F0). Three HR toddlers later classified with an ASD at 36 months (autistic disorder in all cases) produced cries that had among the highest F0 and shortest durations. Taken together these results indicate that toddlers at high risk for ASD (and those with an ASD) express atypical patterns of distress in response a social stressor. Implications for early diagnosis and parenting are discussed.